Safety and effectiveness of linagliptin in Korean patients with type 2 diabetes: A postmarketing surveillance study. Issue 5 (7th February 2021) - Bae, Jaehyun; Song, Kee‐Ho; Park, Jong Suk; Lee, Jae Hyuk; Jeong, In‐Kyung; Kim, Hyun Jin; Lim, Young‐Hyo; Cho, Jae‐Hyoung; Choi, Sung Hee; Chung, Yoon‐Sok; Kang, Eun Seok
Abstract: We designed a postmarketing surveillance study of linagliptin for patients with type 2 diabetes (T2D) in Korea. This prospective, observational, multicentre study investigated the safety and glycaemic effectiveness of linagliptin as monotherapy or combination therapy with other antidiabetic drugs in routine clinical practice. Endpoints were the incidence of adverse drug reactions (ADRs) and the change in HbA1c. Overall, 3119 and 2171 patients were included in the safety and effectiveness analysis sets, respectively. A total of 56 patients (1.8%) experienced ADRs. The most common ADR was gastrointestinal disorders (0.7%), followed by metabolism and nutrition disorders (0.5%). ADRs of special interest, including pancreatic diseases, cardiac diseases and hypoglycaemia, occurred in 12 patients, 11 of whom had hypoglycaemia, while one had a skin lesion. Mean HbA1c change during the study period was −0.8%. Lower body mass index, shorter diabetes duration and higher baseline HbA1c were independently associated with a better effectiveness, while the presence of diabetic complications, dyslipidaemia and the use of sulphonylureas were associated with a poor response. In conclusion, linagliptin showed an excellent safety profile and glycaemic effectiveness in Korean patients with T2D.